Detect plastic litter in Cyprus region using sentinel-2 - Kalogirou, Eleftheria; Makri, Despina; Kountouri, Josefina; Stylianou, Thrasos; Themistokleous, Kyriakos; Papoutsa, Christiana; Melillos, George; Hadjimitsis, Diofantos G. (My University, 2023)
Marine litter is permanent, manufactured or processed solid matter that is disposed of in oceans, rivers, or beaches. Indirectly brought into the sea by rivers, sewage, rainwater and wind, or discarded or lost at sea. Marine litter poses environmental, economic, health, aesthetic and cultural threats. This includes the degradation of marine and coastal habitats and ecosystems, causing socioeconomic losses in the marine sector. Marine litter is characterized by unsustainable production and consumption patterns, poor waste management and infrastructure, and lack of adequate legal and policy frameworks and enforcement (including cross-border trade of plastic waste between regions), and a transnational challenge rooted in a lack of financial resources. This paper aims to detect plastic waste and fish farms. The study was conducted in Limassol, Cyprus, south of the Limassol Old Port. The Sentinel Application Platform (SNAP) was used to conduct the study, using the Sentinel-2 imagery data. We used several well-established indices for water feature extraction to detect plastic litter. The Normalized Difference Water Index (NDWI), Water Ratio Index (WRI), Normalized Difference Vegetation Index (NDVI), Automated Water Extraction Index (AWEI), Modified Normalization Deference Water Index (MNDWI) and Normalization Deference Moisture Index (NDMI), the Simple Ratio (SR). Also, the Plastic Index (PI) and Reversed Normalized Difference Vegetation Index (RNDVI). The results when applying the above indicators are satisfactory and can separate the plastic waste in the sea.
Keywords: Cyprus; Indices; Plastic Litter; Sentinel-2